Drumming among the Akan and Anlo Ewe of Ghana: an introduction - Anku, Willie (International Library of African Music, 2009)
It is generally recognized that the cultivation of music in any given society is limited by its tradition and history. Where ethnicity defines the boundaries of social and cultural life, particular traditions of drumming tend to be similarly confined. As a number of studies have been made of individual Akan and Anlo Ewe drumming styles, which have much in common (see references), it may be useful to offer here a general comparison of stylistic features of these two peoples, for there are also important differences that can be attributed to factors of ethnicity.
Keywords: Anlo (African people); Ewe (African people); Akan (African people); African Music; Ghana; Drumming